Plant-PGPR interaction study of plant growth-promoting diazotrophs Kosakonia radicincitans BA1 and Stenotrophomonas maltophilia COA2 to enhance growth and stress-related gene expression in Saccharum spp. Issue 1 (1st January 2020) - Singh, Rajesh Kumar; Singh, Pratiksha; Li, Hai-Bi; Guo, Dao-Jun; Song, Qi-Qi; Yang, Li-Tao; Malviya, Mukesh Kumar; Song, Xiu-Peng; Li, Yang-Rui
ABSTRACT: Sugarcane is a leading biofuel crop besides being a source of crystal sugar and biomaterials worldwide. This study chiefly focuses on the role of diazotrophic bacteria isolated from sugarcane rhizosphere exhibiting different plant growth-promoting traits and biocontrol activities. Several bacterial isolates were obtained from the rhizosphere soil samples of four sugarcane cultivars. Out of these, 23 strains were selected and identified by 16S rRNA gene sequencing which confirmed different PGP-traits, biocontrol, and nitrogenase activities with nifH gene amplification. Two prominent strains, Kosakonia radicincitans-BA1 and Stenotrophomonas maltophilia-COA2 were selected for further analysis. Biolog plate assay was used to establish the utilization of various carbon and nitrogen sources and pH and osmotic stress tolerance for both strains. Colonization of selected strains in the sugarcane plant was observed by scanning electron microscopy and confocal laser scanning microscopy exhibited bacterial cells were frequently located in sugarcane tissues. Inoculation of the strains in GT11 and GXB9 cultivars led to a significant increase in growth parameters, nitrogen content, expression of nifH, and stress-related genes under greenhouse conditions. This is the first study to explore K. radicincitans and S. maltophilia as nitrogen-fixing plant growth-promoting rhizobacteria in sugarcane for disease management and reduce the practice of chemical fertilizers.